2020
DOI: 10.3390/ijms21093285
|View full text |Cite
|
Sign up to set email alerts
|

Targeting AKT/mTOR in Oral Cancer: Mechanisms and Advances in Clinical Trials

Abstract: Oral cancer (OC) is a devastating disease that takes the lives of lots of people globally every year. The current spectrum of treatment modalities does not meet the needs of the patients. The disease heterogeneity demands personalized medicine or targeted therapies. Therefore, there is an urgent need to identify potential targets for the treatment of OC. Abundant evidence has suggested that the components of the protein kinase B (AKT)/ mammalian target of rapamycin (mTOR) pathway are intrinsic factors for carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(129 citation statements)
references
References 209 publications
(218 reference statements)
3
124
0
2
Order By: Relevance
“…This malignant condition includes cancer of the lip, tongue, mouth, the floor of mouth, and different parts of the oral cavity. [262][263][264] Like other forms of cancer, the aetiology of oral cancer has not been completely elucidated, but it is interesting to mention that, in the light of recent findings, a link between oral microbiota and cancer development has been found. Periodontitis, a disease affecting tooth's supporting tissue, increases the possibility for the development of oral cancer.…”
Section: Oral Cancermentioning
confidence: 99%
“…This malignant condition includes cancer of the lip, tongue, mouth, the floor of mouth, and different parts of the oral cavity. [262][263][264] Like other forms of cancer, the aetiology of oral cancer has not been completely elucidated, but it is interesting to mention that, in the light of recent findings, a link between oral microbiota and cancer development has been found. Periodontitis, a disease affecting tooth's supporting tissue, increases the possibility for the development of oral cancer.…”
Section: Oral Cancermentioning
confidence: 99%
“…Unfortunately, the authors did not attempt to investigate the role of AKT/mTOR in these experiments. Abundant evidence from the published literature demonstrated that components of AKT/mTOR signaling are critical factors for epithelial-to-mesenchymal transition (EMT) during carcinogenesis but some studies also shed a light on the relationships between AKT/mTOR and EndMT [ 158 , 159 , 160 , 161 , 162 ]. Thus, 48-h treatment of HUVEC with TGF-β 1 led to the significant enhancement of EndMT, motility, and migration ability along with the activation of mTORC1/S6K axis [ 163 ].…”
Section: Introductionmentioning
confidence: 99%
“…Harnessing these multimodal mechanisms via immunotherapeutics is therefore expected to be beneficial in early and advanced stages of HCC. Utilizing the differential responses, systemic therapies to perturb VEGF-dependent angiogenesis, WNT, PI3K/AKT/mTOR, AMPK, and c-MET pathways in the TME are either approved or in clinical trials ( 104 ). However, Sorafenib, an oral tyrosine kinase inhibitor (TKI), remains the only FDA-approved treatment with survival benefits for HCC.…”
Section: Targeting Immunity In Hcc: Current Strategies Limitations mentioning
confidence: 99%